2018
DOI: 10.1080/14756366.2018.1501044
|View full text |Cite
|
Sign up to set email alerts
|

Coptisine-induced inhibition ofHelicobacter pylori: elucidation of specific mechanisms by probing urease active site and its maturation process

Abstract: In this study, we examined the anti-Helicobactor pylori effects of the main protoberberine-type alkaloids in Rhizoma Coptidis. Coptisine exerted varying antibacterial and bactericidal effects against three standard H. pylori strains and eleven clinical isolates, including four drug-resistant strains, with minimum inhibitory concentrations ranging from 25 to 50 μg/mL and minimal bactericidal concentrations ranging from 37.5 to 125 μg/mL. Coptisine’s anti-H. pylori effects derived from specific inhibition of ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…Chelerythrine chloride is considered to be the most potential inhibitor of urease, with the lowest IC 50 and K i values and the highest binding energy. Li et al [ 34 ] demonstrated that when the final concentration of H. pylori UreG was 5 μM, the IC 50 value of coptisine was 89.86 μM. In this study, the IC 50 value of coptisine chloride was 86.62 μM, with a final concentration of 3 μM UreG, and the IC 50 value of 18.13 μM for chelerythrine chloride was significantly lower than that of coptisine chloride.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Chelerythrine chloride is considered to be the most potential inhibitor of urease, with the lowest IC 50 and K i values and the highest binding energy. Li et al [ 34 ] demonstrated that when the final concentration of H. pylori UreG was 5 μM, the IC 50 value of coptisine was 89.86 μM. In this study, the IC 50 value of coptisine chloride was 86.62 μM, with a final concentration of 3 μM UreG, and the IC 50 value of 18.13 μM for chelerythrine chloride was significantly lower than that of coptisine chloride.…”
Section: Discussionmentioning
confidence: 41%
“…Yang et al [ 45 ] first proposed and confirmed that targeting the metallochaperone UreG to design urease inhibitors could disrupt the urease maturation process, and provided two effective urease inhibitors of colloidal bismuth against H. pylori activity only through UreG, not apo-urease. Li et al [ 34 ] demonstrated that coptisine inactivation of H. pylori urease involved binding to the urease active site sulfhydryl group and accessory protein UreG. These results show the potential of UreG serving as a target for developing urease inhibitors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, coptisine (50 μmol/L, 0‐120s) was revealed to reduce S.aureus adhesion and inhibit PfDHODH, an anti‐malarial chemotherapy target . Coptisine (50‐200 μmol/L, 30 minutes) also exhibits anti‐H.pylori effect through the inhibition of urease activity, suggesting coptisine was a promising drug for digestive diseases . Moreover, Zhang et al built a nude mouse model of chemotherapy‐related diarrhoea by using irinotecan, and the result showed coptisine (30 mg/kg, oral, twice a day, 4 days) was able to reduce the degree of diarrhoea and ileum mucosal injury through modulating IκBα/NF‐κB signalling pathway .…”
Section: Anti‐bacterial Propertymentioning
confidence: 99%
“…It can be used to relieve bacterial dysentery, gynecological inflammation and urinary tract-related surgical infections on clinic ( Yokozawa et al., 2005 ; Wang et al., 2017 ). It has been the subject of scientific interest in recent years due to its multiple antibacterial, antiviral, and gastrointestinal protection biological activities ( Li et al., 2018 ; Chen et al., 2020 ). However, the largely potential anti-gastritis mechanism of Pal remain unknown, and whether Pal can be safely and effectively used in clinical still needs more investigation.…”
Section: Introductionmentioning
confidence: 99%